The Clinical and Economic Implications of Running a Psychiatric Outpatient Facility without the Continued Presence of a Psychiatrist - Berg, John E. (Advances in Social Sciences Research Journal, 2025)
Recruitment of psychiatrists to remote areas of a country is difficult. The consequence is seen clinically, patients do not get qualified care, and the facilities pay a lot for maintaining a rudimentary service. This is illustrated with data from an outpatient facility set up with one position as psychiatrist. The cost of maintaining the role of a psychiatrist by four stand-ins is the double of what one single doctor would cost, NOK 2,070,000 versus NOK 950,000 (NOK 100 = $12.50). The decisions made by four is difficult to streamline for patients at the facility and they encounter non-congruent treatment options.